Liquid level process monitoring system using SCADA software / Ismawati Ismail - Ismail, Ismawati (2008)
Liquid level monitoring system is a system to monitor and control the level of liquid inside a tank using SCADA. The system is implemented through the integration of hardware and software parts. The hardware part covers the process of building a tank and control circuit. This project uses water level as its variable and ultrasonic sensor as a device to measure the water level. The ultrasonic sensor is mounted at the top of the tank without physical contact with the liquid material. Ultrasonic sensor is the leading sensor technologies in liquid level tank measurement and control operations and it uses the propagation time of a sound pulse to calculate the distance of a target. For that reason, ultrasonic sensor is the best tool to measure the amount of water inside the tank and distance to the surface of the liquid. The hardware part is connected to the Programmable Logic controller (PLC). PLC is connected to the personal computer (PC) by using RS- 232 USB cables. CX-Programmer will be used to program the PLC and the Lookout software from National Instrumentation to develop a SCADA system.